Uma proposta de intervenção gerencial para a inserção dos egressos de cursos técnicos do IFES campus Guarapari no mercado de trabalho local - Carvalho Junior, José Roberto Abreu de (2018)
The Federal Institutes of Education, Science and Technology (IFs) were created to offer Brazilian society a quality education aligned with the practice of research and extension. Its activity area is professional education. One of the purposes of these institutions is preparing the citizen in a human and professional formation targetting a work in the labor market, considering the local productive arrangements. Considering this, it is hoped to leverage the socioeconomic development of the municipalities and regions where IFs are located. In this scenario, the Federal Institute of Espírito Santo (Ifes) - Campus Guarapari, located in the municipality of the same name, in the state of Espírito Santo, is one of the 644 existing units that currently make up the Federal Professional Education Network. This study aimed to diagnose if the graduates of technical courses at this institution are entering the local labor market as technical professionals. Egresses represent an important source of information for evaluating the effectiveness of public policies, especially educational ones. It is characterized as a descriptive study type. The research subjects are represented by a population of 650 graduates from the technical courses in Administration and Electrotechnology - formed between the years 2011 and 2017 - and by a sample of 4 managers of this Ifes campus. The data collection instruments used were the questionnaire and the interview. It is considered a quantitative and qualitative data analysis approach. The results showed that 56.6% of the graduates were working, but only 10% of them worked as technicians in their training area; 96.8% evaluated as good or excellent the quality of the course carried out at the institution; and that the Campus Guarapari do Ifes does not carry out monitoring of its graduates. As a technical product resulting from this study, aligned with the Research Line Operations Management in the Public and aiming at contributing to the solution of the detected problem, a proposal of intervention using the 5W2H administrative tool is presented to this organization.